Burst failure characteristics of coal under different loading conditions based on acoustic emission monitoring - Zhen Hao; Zijun Han; Xiaochang Li; Xiaobin Li; Lei Guo (Scientific Reports)
Abstract With the increasing depth and intensity of coal mining, the frequency of burst failures has risen sharply, becoming a critical issue affecting the safety and efficiency of coal mines. This paper analyzes the burst failure characteristics of coal under different loading conditions using triaxial tests and acoustic emission (AE) monitoring. Three loading rates and confining pressures were used to investigate the behavior of coal samples. The AE signals during triaxial compression exhibited three distinct stages: the quiet period, eruption period, and post-peak release period. During the quiet period, fissures in the coal sample closed, and elastic deformation occurred, resulting in low AE counts as most of the compression energy was converted into elastic energy. In the eruption period, cracks propagated and connected, forming macroscopic fractures, accompanied by explosive growth in AE counts and energy, which peaked at maximum stress. During the post-peak release period, AE signals weakened or even disappeared as stress decreased. Both loading rate and confining pressure have significant influence on the burst failure of coal samples. For the same confining pressure, higher loading rates reduced AE counts but increased energy peaks, leading to more severe damage. For the same loading rate, lower confining pressures increased AE counts and energy peaks, exacerbating damage. AE counts were notably higher in the top part of the samples compared to the lower part. Both loading rate and confining pressure can induce large energy events and lead to the failure of the coal sample.